Phalaenopsis CULTIVATION IN DIFFERENT MEDIA. PART I. GROWTH AND FLOWERING - Tomasz Trelka; Włodzimierz Breś; Agata Kozłowska (Acta Scientiarum Polonorum: Hortorum Cultus, 2010)
The production costs force the orchids growers to look for media that could become an alternative for the basic ones. Phalaenopsis plants (ex in vitro) were planted into containers filled with different media: New Zealand sphagnum moss, mixture of expanded clay pellets and New Zealand sphagnum moss (v:v = 1:1) and expanded clay pellets. Originally, orchids were grown in translucent plastic pots of 7 cm diameter (8,5 months) and then, they were transferred to translucent plastic pots of 11 cm diameter and 0.5 dm3 capacity. Effect of medium on the size of plant, hydratation of leaves tissue and flowering was evaluated. Orchids grown in New Zealand sphagnum moss create a significantly greater mass of the aboveground plant part and the roots. Also parameters characterizing the inflorescence and flowers indicate that the most favorable for the orchids is to grow them in sphagnum moss. The least favorable growth conditions were provided by the growing in expanded clay pellets without any additions. In this medium, only 25 to 35% of plants flowered.